Clinical features of three patients with paradoxical immune reconstitution inflammatory syndrome associated with Talaromyces marneffei infection - Nguyen Tat Thanh; Le Duc Vinh; Nguyen Thanh Liem; Cecilia Shikuma; Jeremy N. Day; Guy Thwaites; Thuy Le (Medical Mycology Case Reports, 2018)
Talaromyces marneffei infection is a major cause of death in HIV-infected individuals in South and Southeast Asia. Talaromycosis immune reconstitution inflammatory syndrome has not been well described. Here we report the clinical features, management, and outcomes of three HIV-infected patients with talaromycosis-associated paradoxical immune reconstitution inflammatory syndrome in Ho Chi Minh City, Vietnam.